2018
DOI: 10.1596/978-1-4648-1286-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Liberia's Transport Connectivity and Potential Growth

Abstract: Books in this series are published to communicate the results of Bank research, analysis, and operational experience with the least possible delay. The extent of language editing varies from book to book. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Additionally, many studies propose new tools, guidelines, and methodologies of collecting data, projecting theoretical outcomes, and advising evidence-based policy and decision making [1,57,60,[63][64][65]. Further, many sources concur that governments have overlooked the importance of transport services, unrealistically expecting the private sector to fill this gap [7,47,66]. Lastly, despite trends toward decentralization of governance and support of localized government within recent years [56], the poorest of the poor continue to miss out on the benefits of infrastructure and transport-based investments [7,58].…”
Section: Policy and Governance Impact And Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, many studies propose new tools, guidelines, and methodologies of collecting data, projecting theoretical outcomes, and advising evidence-based policy and decision making [1,57,60,[63][64][65]. Further, many sources concur that governments have overlooked the importance of transport services, unrealistically expecting the private sector to fill this gap [7,47,66]. Lastly, despite trends toward decentralization of governance and support of localized government within recent years [56], the poorest of the poor continue to miss out on the benefits of infrastructure and transport-based investments [7,58].…”
Section: Policy and Governance Impact And Implicationsmentioning
confidence: 99%
“…Yet, bridges are an integral part of many countries' transportation systems, such as in Nepal, where over 7500 rural bridges exist and 450 more bridges are expected to be built every year. Similarly, bridges are critical infrastructure in Liberia, where there is an average of one bridge and three culverts per five kilometers of road [66,158]. In response to this gap left by governments and institutions, the rural bridge niche of the rural transportation sector is led largely by small NGOs.…”
Section: Rural Bridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though universal rural access to all weather roads cannot be provided in all countries by 2030, other solutions exist in the meantime to improve social integration. When rural paved roads are not affordable, other options could include investing in cabotage in coastal areas (Iimi and Rao, 2018), or smaller roads better suited for bicycles and motorcycle traffic (Raballand et al, 2010).…”
Section: Solutions For Rural Integration If Paved Roads Are Not Affordablementioning
confidence: 99%
“…Similar to most rural areas of Sub-Saharan Africa, rural accessibility is very low in the Zambezia and Nampula provinces of Mozambique and most farmers practice subsistence agriculture ( 2 ). A recent study found that in these two regions, even if all existing roads were upgraded, connectivity would not exceed 40% ( 3 ).There is thus an urgent need for transport investments. Improving farmers’ connectivity to markets would increase their revenues and reduce poverty, while also improving the national economy ( e.g .…”
mentioning
confidence: 99%